EFEKTIVITAS PEMBERIAN REWARD MELALUI METODE TOKEN EKONOMI UNTUK MENINGKATKAN KEDISIPLINAN ANAK USIA DINI - Mufidah, Umri (BELIA: Early Childhood Education Papers, 2012)
Dicipline is one of the to remedy a mistaken behaviour. Dicipline does encourge guide, and help children togain a feeling of contenment through loyality obdience, and educate children to think on a regular basis.Hurlock states that in childhood stage, appreciation has its own instructive value. Everytime children showtheir submission, a reward or token economy which can be collected and later be exchanged with sometningvaluable. The aim of this study is to find out wheter or not this token economy is effective in increasing childrendicipline. This research is a quasi experiment nonequivalent control group design. The sampling techniquewhich is conducted is nonprobability sampling, although kind of sample that use in this experimen is purposivesampling. The t-pairedÂ  posttest of experimented and controled group resulting some proof that show significantdifferences because it has < 0,05 significant value (2-tailed), wich is 0,00 meaning that there are significantdifferences. Based on t-count was 9,470 > was the 2,065 showed that there was diferrence result posttestexperiment group and control group, which experiment group produces value of posttest higher than controlgroup